Konsep Akad ' Seadanya ' dalam Sistem Perdagangan Masyarakat Banjar Kalimantan Selatan - Badrian; Muhammad Rizali; Pati Matu Zahra; Fithriana Syarqawie; Anwar Hafidzi; Khairatun Hisanah Alpasa (Program Studi Ekonomi Syariah IAI Darul Ulum Kandangan, 2023)
This journal examines the customary practices of the Banjar community in conducting